Factibilidad De Firmar Un Tratado De Libre Comercio Entre Colombia Y La República Popular De China (2023)
This paper provides information on FTAs (Free Trade Agreements), the WTO (World Trade Organization), which is the supranational organization that governs these agreements and grants dispute resolution mechanisms. In addition, this paper proposes a possible negotiation of an FTA between Colombia and the People’s Republic of China, which analyzes the points that are convenient for the economy, advantages, and disadvantages of such anagreement